Alprazolam Poisoning - Kakkar, Ankita; Kumar, Sushil (Journal of Indian Academy of Forensic Medicine, 2015)
Alprazolam is a triazolo benzodiazepine which has antidepressant properties. It is a short acting  anxiolytic of the benzodiazepine class of psychoactive drugs. Alprazolam like other benzodiazepines  binds to specific sites on the gamma-amino-butyric acid (GABA) receptors. Its therapeutic index being  high, it is generally considered a safe and effective drug for the treatment of anxiety disorders and panic  attack. Alprazolam has since long been consumed as drug of abuse, however trend to use it for suicidal  purpose is recently rising, in which easy availability of this drug plays a significant role. It is available for  oral administration in compressed tablet and extended release capsule formulations. We report one such case of alprazolam poisoning in which the drug was easily available. As is  evident from this report documentation, inability to confront persistent domestic problems, and failure to  achieve life’s goals were the triggering factors in a middle aged female, to compel her to suicide with the  help of alprazolam, which was available to her as prescribed by a physician for her ailment.
Keywords: Abuse; Availability; Psychotic; Triggering; Suicide